Promoting Peaceful and Inclusive Information Security Compliance: A Systematic Review of Assurance Behavior in IT Employees within the Context of SDG-16 in Malaysia - Zarilla, Aziela Isma (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
This systematic review examines the alignment between IT employees' desire,intention, and compliance with information security protocols, a critical issue in Malaysia wherehuman error is a leading cause of data breaches. Situated within the context of SustainableDevelopment Goal 16 (SDG-16), the study analyzes 30 peer-reviewed articles to identify keybehavioral factors. Findings indicate that while training improves knowledge, its impact on longterm behavior is limited. A significant compliance gap is driven by psychological factors likework overload and optimism bias, as well as organizational elements such as culture andmanagement support. The review concludes that effective information security assurancerequires a holistic strategy integrating tailored, ethical training with strong organizational supportto mitigate psychological strain and foster a robust security culture. This approach is essentialnot only for strengthening cybersecurity but also for supporting Malaysia's commitment to digitalresilience and the principles of SDG-16.